Efek Maturity, Buku Bunga serta Undian pada Peralihan Corporate Obligation Price yang Terakhir dalam BEI Periode Skala 2019 - 2021 - Nurfaindah Lestari; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of maturity, interest rates and coupons on changes in corporate bond prices. This study uses secondary data from annual financial reports. Data collection methods use statistical dataset methods, where data collection is carried out based on data access techniques published by the company. The population in this study is all financial sectors listed on the Indonesian stock exchange in 2019-2021, namely 509, with a total sample of 10 companies that meet several predetermined criteria. The sampling technique used in this study is the target sampling method. The data analysis technique used is multiple linear regression. The results showed that maturity and interest rates had no significant effect on changes in corporate bond prices, while Coupons had a significant effect on changes in corporate bond prices.Keywords: Maturity, interest rate, corporate bond coupon.